A new workflow combining magnetic cell separation and impedance-based cell dispensing for gentle, simple and reliable cloning of specific CD8+ T cells - Myriam Ben Khelil; Luc Aeberli; Marie Perchaud; Raphael Genolet; Syrine Abdeljaoued; Christophe Borg; Delphine Binda; Alexandre Harari; Camilla Jandus; Georges Muller; Romain Loyon (SLAS Technology, 2022)
Reverse immunology has open the door to innovative cancer immunotherapy strategies such as immunogenic antigen-based vaccination and transgenic T cell receptor (TCR)-based adoptive cell transfer. This approach enables the identification of immunogenic tumor specific antigen derived peptides. One of the major challenges is the rapid selection of antigen-specific CD8+ T cell clones. Thus, IFNγ-producing CD8+ T cells magnetic sorting combined with limiting dilution cloning approach represents the most common method of specific T cell cloning. However, during plate setup several wells will not contain T cells whereas others will contain mixed population of T cells. In this case, a re-cloning step is required which make limiting dilution based cloning a laborious, inefficient, expensive and a time-consuming method. To address these obstacles, here we present a novel 2-step workflow combining simple, affordable and gentle magnetic cell separation followed by single cell isolation using a device called DispenCell-S1. We aimed to compare this new workflow with the traditional limiting dilution method using in vitro generated antigen-specific CD8+ T cells. Herein, we reported the reliability of DispenCell-S1 method and its efficiency in T cell clones isolation.